Knowledge about Disease and Health Behaviours in Elderly Stroke Survivors as a Context of Occupational Therapy Implementations - Okrasa Julia; Guszkowska Monika (Physical Culture and Sport: Studies and Research)
Knowledge the risk factors and symptoms of strokes is important in the context of a quick response to first signals and secondary prevention, and health education is one of the tasks of the neurological occupational therapist. To carry out this task, the therapist needs information about patients’ health behaviours and knowledge about the disease. This study aimed to determine: 1. elderly patients’ knowledge about strokes and the channels of knowledge transmission; 2. differences between their pre- and post-stroke health behaviours; 3. differences in knowledge and health behaviours depending on the respondent’s gender, age and education.